Resistance of Students from Migrant Worker Families Towards the Internalization of Mubadalah Values In Islamic Education - Mochammad Zaka Ardiansyah; Mulyadi; Jamilah; Akhmad Nurul Kawakip (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
Despite the growing emphasis on gender equality in Islamic education, limited research has examined how students from migrant worker families respond to the internalization of Mubadalah values. This study aims to examine the forms of resistance demonstrated by students who are children of migrant workers. Employing a qualitative approach with a case study design, the research was conducted in four Islamic educational institutions located in Jember, East Java, Indonesia. Data were collected through in-depth interviews and analyzed using the interactive model of data analysis. The findings reveal that students exhibit two forms of resistance: overt resistance and covert resistance toward gender equality practices. Overt resistance is manifested in the rejection of domestic tasks perceived as incompatible with traditional gender roles, while covert resistance appears in the form of avoidance, lack of enthusiasm, and passive participation. In conclusion, resistance to the internalization of Mubadalah values emerges from the interaction between educational interventions and the socio-cultural backgrounds of students. Therefore, pedagogical strategies that are context-sensitive are required, integrating gender equality values with students’ lived experiences and family norms. This study contributes to the advancement of Islamic education scholarship and offers practical recommendations for strengthening gender equality education in Islamic educational institutions.